2018
DOI: 10.3324/haematol.2018.199448
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity reactions to asparaginase in mice are mediated by anti-asparaginase IgE and IgG and the immunoglobulin receptors FcεRI and FcγRIII

Abstract: Asparaginase is an important drug for the treatment of leukemias. However, anti-asparaginase antibodies often develop, which can decrease asparaginase drug levels and increase the risk of relapse. The aim of this study is to identify the immunoglobulin isotypes and receptors responsible for asparaginase hypersensitivities. Mice immunized with asparaginase developed anti-asparaginase IgG1 and IgE antibodies, and challenging the sensitized mice with asparaginase induced severe hypersensitivity reactions. Flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 41 publications
6
29
1
1
Order By: Relevance
“…Previously, we demonstrated that ASNase-specific recognition and hypersensitivity in mice are Fc-gRIIIdependent, suggesting that soluble anti-ASNase antibodies are required for both to occur (19). In agreement with our previous findings, we found that the binding of ASNase to leukocytes, including B cells and basophils, is significantly decreased after removing soluble antibodies (Supplemental Fig.…”
Section: Asnase Ics Are Detected After Asnase Hypersensitivity In Micesupporting
confidence: 92%
See 4 more Smart Citations
“…Previously, we demonstrated that ASNase-specific recognition and hypersensitivity in mice are Fc-gRIIIdependent, suggesting that soluble anti-ASNase antibodies are required for both to occur (19). In agreement with our previous findings, we found that the binding of ASNase to leukocytes, including B cells and basophils, is significantly decreased after removing soluble antibodies (Supplemental Fig.…”
Section: Asnase Ics Are Detected After Asnase Hypersensitivity In Micesupporting
confidence: 92%
“…Pooled eluate samples were lyophilized overnight and reconstituted with 100 ml of sterile water. Murine anti-ASNase IgG concentrations were determined using a Bovine Serum Albumin Kit (Thermo Fisher Scientific), and confirmation of anti-ASNase IgG antibody activity was demonstrated by ELISA (18,19).…”
Section: Anti-asnase Igg Antibody Purification and Characterization Bmentioning
confidence: 99%
See 3 more Smart Citations